The Value of Imaging and Composition-Based Biomarkers in Duchenne Muscular Dystrophy Clinical Trials - Chrzanowski, Stephen M. (Neurotherapeutics, 2019)
As the drug development pipeline for Duchenne muscular dystrophy (DMD) rapidly advances, clinical trial outcomes need to be optimized. Effective assessment of disease burden, natural history progression, and response to therapy in clinical trials for Duchenne muscular dystrophy are critical factors for clinical trial success. By choosing optimal biomarkers to better assess therapeutic efficacy, study costs and sample size requirements can be reduced. Currently, functional measures continue to serve as the primary outcome for the majority of DMD clinical trials. Quantitative measures of muscle health, including magnetic resonance imaging and spectroscopy, electrical impedance myography, and ultrasound, sensitively identify diseased muscle, disease progression, and response to a therapeutic intervention. Furthermore, such non-invasive techniques have the potential to identify disease pathology prior to onset of clinical symptoms. Despite robust supportive evidence, non-invasive quantitative techniques are still not frequently utilized in clinical trials for Duchenne muscular dystrophy. Non-invasive quantitative techniques have demonstrated the ability to quantify disease progression and potential response to therapeutic intervention, and should be used as a supplement to current standard functional measures. Such methods have the potential to significantly accelerate the development and approval of therapies for DMD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-019-00825-1) contains supplementary material, which is available to authorized users.